2006
DOI: 10.1111/j.1600-6143.2005.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Long-Term Outcome of Transplant Renal Artery Stenosis in Adult Recipients After Treatment by Percutaneous Transluminal Angioplasty

Abstract: Transplant renal artery stenosis (TRAS) is a common complication of kidney transplantation but attempts to identify predisposing risk factors for TRAS have yielded conflicting results. In order to determine the predisposing factors for transplant (TRAS), we retrospectively reviewed the records of 29 renal allograft recipients with TRAS treated with percutaneous transluminal angioplasty (PTA). The TRAS group was compared with a case-control group of 58 patients. Predisposing factors for TRAS included CMV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
4
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 29 publications
3
98
4
4
Order By: Relevance
“…CMV seropositivity was also linked to restenosis after coronary angioplasty and atherectomy (116). Similarly, in renal transplantation, CMV infection was an independent risk factor in a multivariate analysis of arterial stenosis (117)(118)(119). Such clinical studies are often confounded by difficulties in interpreting serologic data, notably after transplantation; by often unknown timing of CMV infections; and by variability in prophylactic strategies.…”
Section: Nonimmune Pathways In Cmv-associated Allograft Injurymentioning
confidence: 99%
“…CMV seropositivity was also linked to restenosis after coronary angioplasty and atherectomy (116). Similarly, in renal transplantation, CMV infection was an independent risk factor in a multivariate analysis of arterial stenosis (117)(118)(119). Such clinical studies are often confounded by difficulties in interpreting serologic data, notably after transplantation; by often unknown timing of CMV infections; and by variability in prophylactic strategies.…”
Section: Nonimmune Pathways In Cmv-associated Allograft Injurymentioning
confidence: 99%
“…6 estenose de artéria renal transplantada. 9 Os indicadores clínicos de EART são hipertensão de início súbito ou refratária e/ou disfunção do enxerto, com aumento dos níveis de creatinina. A presença dessas alterações deve ser a principal indicação de tratamento.…”
Section: Discussionunclassified
“…9,18 Diversos estudos têm relatado taxas menores, menos de 10%, quando realizado angioplastia com stent primário. 19 Observou-se reestenose em 100% dos pacientes tratados somente com angioplastia por balão (3/3) e em 16% dos pacientes que realizaram colocação de stent na primeira abordagem (4/25).…”
Section: Discussionunclassified
“…In a retrospective study of 29 recipients with stenosis and a case-control group of 58 patients, an increased risk of stenosis was significantly associated with CMV infection and delayed function. [38] In contrast to termino-terminal anastomosis with the internal iliac artery, termino-terminal anastomosis with the external iliac artery, in children, decreases renal artery stenosis incidence.…”
Section: Posttransplant Hypertension Due To Renal Transplant Artery Smentioning
confidence: 99%
“…It has been suggested that functionally significant stenosis occurs in up to 12 percent of transplant recipients with hypertension, with a range of incidence from 1 to 23 percent. [38] As with other causes of bilateral renal artery stenosis or unilateral stenosis in a solitary kidney, the administration of an angiotensin converting enzyme (ACE) inhibitor or angiotensin II receptor blocker (ARB) to a patient with transplant renal artery stenosis can lead to a reversible decline in glomerular filtration rate. [39,41] Thus, an elevation in plasma creatinine concentration in this setting is suggestive but not diagnostic of renovascular disease in the graft.…”
Section: Posttransplant Hypertension Due To Renal Transplant Artery Smentioning
confidence: 99%